Change in hyper-palatable food availability in the US food system over 30 years: 1988-2018 - Saron Demeke; Kaitlyn Rohde; Lynn Chollet-Hinton; Cassandra Sutton; Kai Ling Kong; Tera L Fazzino (Cambridge University Press, 2023)
Abstract Objective: To quantify the change in availability of hyper-palatable foods (HPF) in the US foods system over 30 years (1988-2018). Design: Three datasets considered representative of the US food system were used in analyses to represent years 1988, 2001 and 2018. A standardised definition from Fazzino et al. (2019) that specifies combinations of nutrients was used to identify HPF. Setting: Analysis of food-item level data was conducted. Differences in the prevalence of HPF were characterised by Cochran's Q and McNemar's tests. Generalised linear mixed models with a fixed effect for time and random intercept for food item estimated change in the likelihood that a food was classified as hyper-palatable over time. Participants: No participant data were used. Results: The prevalence of HPF increased 20 % from 1988 to 2018 (from 49 % to 69 %; P < 0·0001). The most prominent difference was in the availability of HPF high in fat and Na, which evidenced a 17 % higher prevalence in 2018 compared with 1988 (P < 0·0001). Compared with 1988, the same food items were >2 times more likely to be hyper-palatable in 2001, and the same food items were >4 times more likely to be classified as hyper-palatable in 2018 compared with 1988 (P values < 0·0001). Conclusions: The availability of HPF in the US food system increased substantially over 30 years. Existing food products in the food system may have been reformulated over time to enhance their palatability.